Maggots in Medicine: A Narrative Review Discussing the Barriers to Maggot Debridement Therapy and Its Utilisation in the Treatment of Chronic Wounds - Yamni Nigam (Journal of Clinical Medicine, 2024)
Background: There is currently no standardised guidance that supports any particular method of debridement. Maggot debridement therapy (MDT) is often used as a last-resort therapy over more conventional treatments, despite mounting evidence of its benefits. Objectives: This review aimed to critically analyse the systemic and individual barriers to MDT implementation and utilisation. As the primary providers of wound care, discussions are primarily focused on nursing care. Search strategy: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was used to conduct a literature search of the studies published between 2012 and 2022 across four databases: CINAHL, Cochrane, British Nursing Index and PubMed. The keywords used for this search were based on the PICO (Population, Intervention, Comparison, Outcome) framework. Twenty-three main articles met the inclusion criteria. All the studies were quality appraised using a risk of bias tool and data were extracted using a predesigned form. The evidence base of the four main themes were discussed: (1) effectiveness of MDT compared to conventional treatments, (2) perceptions and stigma, (3) cost, training and accessibility and (4) side-effects. Conclusions: The findings of this review suggest that MDT is an underused and potentially very effective method of debridement compared to conventional treatments. The identified barriers could be mitigated with relatively low-cost solutions. More high-quality research is needed across all the barriers.